Nucleic acid aptamers in cancer research, diagnosis and therapy. (7th March 2015) - Ma, Haitao; Liu, Jinping; Ali, M. Monsur; Mahmood, M. Arif Iftakher; Labanieh, Louai; Lu, Mengrou; Iqbal, Samir M.; Zhang, Qun; Zhao, Weian; Wan, Yuan
<x xml:space="preserve">Abstract</x> A comprehensive, up-to-date aptamer review with a specific focus on the cancer field.